If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -6) + 14(y + 10) = 0 Reorder the terms: 4(-6 + y) + 14(y + 10) = 0 (-6 * 4 + y * 4) + 14(y + 10) = 0 (-24 + 4y) + 14(y + 10) = 0 Reorder the terms: -24 + 4y + 14(10 + y) = 0 -24 + 4y + (10 * 14 + y * 14) = 0 -24 + 4y + (140 + 14y) = 0 Reorder the terms: -24 + 140 + 4y + 14y = 0 Combine like terms: -24 + 140 = 116 116 + 4y + 14y = 0 Combine like terms: 4y + 14y = 18y 116 + 18y = 0 Solving 116 + 18y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-116' to each side of the equation. 116 + -116 + 18y = 0 + -116 Combine like terms: 116 + -116 = 0 0 + 18y = 0 + -116 18y = 0 + -116 Combine like terms: 0 + -116 = -116 18y = -116 Divide each side by '18'. y = -6.444444444 Simplifying y = -6.444444444
| -a-2a=-24 | | K-17.8=-3 | | 6d=78 | | -17p=0102 | | 15-=y/7 | | x+(x+-38)=180 | | -2(r+4)=24 | | 3(a-4)+15=13 | | 12p=15 | | 4(x-6)+14(x+10)= | | 129=15 | | 240=(5*w*2)+(w*2) | | 89=0.9d+71 | | 408b=36 | | (3/10)*(5/3) | | 5(5x+7)-12x= | | 8.1=-7a+2.1 | | M-11=43 | | x^2+7+9=3 | | f(-4)=9x+8 | | 9-(2y-3)=1-3y | | y-7=-1/2(x-4) | | (3x-9i)(x-3i)=0 | | 7(4y+5)=19y+8 | | 2y+y+9y= | | 15y=6y^2 | | a+1+a+3+2a=180 | | 1+3s=4 | | a+1+a+3+2a=90 | | x*y=31 | | 16f=1.8+32 | | c=2a+3 |